2006
DOI: 10.1074/jbc.m602973200
|View full text |Cite
|
Sign up to set email alerts
|

A New Rubisco-like Protein Coexists with a Photosynthetic Rubisco in the Planktonic Cyanobacteria Microcystis

Abstract: Two genes encoding proteins related to large subunits of Rubisco were identified in the genome of the planktonic cyanobacterium Microcystis aeruginosa PCC 7806 that forms water blooms worldwide. The rbcL I gene belongs to the form I subfamily typically encountered in cyanobacteria, green algae, and land plants. The second and newly discovered gene is of the form IV subfamily and widespread in the Microcystis genus. In M. aeruginosa PCC 7806 cells, the expression of both rbcL I and rbcL IV is sulfur-dependent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 44 publications
0
34
2
Order By: Relevance
“…9 does not explain the presence of RLPs in the picoeukaryote marine chlorophyte O. tauri, which encodes two distinct and highly divergent RLPs in its nuclear genome (17) in addition to a typical form I large The other unusual prokaryote-to-eukaryote lateral transfer in this scheme, which explains the presence of form II RubisCO in the Dinophyceae, has been previously analyzed in detail (44,51,52,58). The archaeal origin model of RubisCO/RLP evolution proposed here is substantially different from that reported previously by Ashida et al (7) and Carre-Mlouka et al (11), who speculated that bona fide RubisCOs arose in the YkrW lineage. However, those authors relied on much smaller sets of sequences and more limited numbers of phylogenetic reconstructions to reach their conclusions.…”
Section: Probing the Evolutionary Origins Of Rubisco: Evidence For Arcontrasting
confidence: 54%
See 3 more Smart Citations
“…9 does not explain the presence of RLPs in the picoeukaryote marine chlorophyte O. tauri, which encodes two distinct and highly divergent RLPs in its nuclear genome (17) in addition to a typical form I large The other unusual prokaryote-to-eukaryote lateral transfer in this scheme, which explains the presence of form II RubisCO in the Dinophyceae, has been previously analyzed in detail (44,51,52,58). The archaeal origin model of RubisCO/RLP evolution proposed here is substantially different from that reported previously by Ashida et al (7) and Carre-Mlouka et al (11), who speculated that bona fide RubisCOs arose in the YkrW lineage. However, those authors relied on much smaller sets of sequences and more limited numbers of phylogenetic reconstructions to reach their conclusions.…”
Section: Probing the Evolutionary Origins Of Rubisco: Evidence For Arcontrasting
confidence: 54%
“…This conundrum was recently addressed, with two possibilities considered: (i) form III archaeal RubisCO preferentially uses an alternative substrate and does not require RuBP for catalysis, or (ii) alternative means to synthesize RuBP that are unique to archaea exist. The first possibility, if true, would also suggest that RuBP-dependent RubisCO activity might have evolved from a protein that possessed some alternative activity, a theory espoused by those that believe that RLP is an evolutionary precursor to RubisCO (7,11). However, exhaustive studies have thus far found no alternative to RuBP as a substrate or CO 2 acceptor for archaeal (or any other) RubisCO (26), suggesting that it is unlikely that form III RubisCO is being used for anything other than producing 3-phosphoglyceric acid (PGA) from RuBP and CO 2 .…”
Section: Physiological Role For Archaeal (Form Iii) Rubiscomentioning
confidence: 99%
See 2 more Smart Citations
“…MTR-1-P isomerase was assayed in a coupling reaction with MtnB and MtnW, previously identified as MTRu-1-P dehydratase and 2,3-diketo-5-methylthiopentyl-1-phosphate enolase respectively. 2,7,15) In this assay, the reaction product MTRu-1-P is converted to 2-hydroxy-3-keto-5-methylthiopentenyl-1-phosphate (HK-MTPenyl-1-P) by sequential reactions of MtnB and MtnW. The reaction was started by adding 2 mM MTR-1-P to a mixture containing 50 mM Tris-HCl buffer (pH 8.1), 1 mM MgCl 2 , 0.5 mg of MTR-1-P isomerase, 5 mg of MtnB, and 15 mg of MtnW.…”
Section: )mentioning
confidence: 99%